OUTLINE OF THE WORKERS CO-OPERATIVE ACT IN JAPAN - Kurimoto, Akira (International Journal of Cooperative Law, 2025)
TheJapanese co-operativelegislationis characterized by the separatelawsthat are specializing to regulate the particular categories of co-operatives andenacted in line with the industrial policies,and the strong government’s control on incorporation and business activities.The Industrial Co-operativeAct of 1900 was a uniform law following the German model and provided for the legal frameworkofcredit, supply, marketing and production1co-operatives.After the Second World War, the allied force introduced the radical land reform as a part ofeconomic democratization programsand helped to enact the Agricultural Co-operative Actin 1947 to cement the effects of reform through organizing farmers in agriculturalco-operatives. Then, the other co-operative lawswere enacted in line with industrial policies (fishery, forestry, banking, SMEsetc.) during 1948-1978. The exception was the Consumer Co-operativeAct of 1948 that placedserious impediments to co-operative activities including the complete prohibition of non-member business, the limitation of operating areas within a prefecture and the lack of credit business.As a result, there are more than 10 co-operative laws inJapanthat enable governmentstomake the strongcontrolover co-operative activitiesfor matters related to organization law as well as business laws. Such legal-administrative system based on laws and regulating ministries has resulted in the emergence of different organizational culture and politicalorientation of co-operativeswhile it contributed to the creation offragmented political economy dominated by the iron triangle of ministries, legislature and trade associations (Masahiko Aoki’s compartmentalized pluralism). It has been very convenient to ministries but might resulted in the lack ofidentityasa co-operative sector. After nearly 30 years efforts, the Workers Co-operative Act (WCA) passed the Diet on December 4th, 2020.WCA has some unique features compared to the existing laws and may give impacts to the existing co-operativelaws.This paper describes the brief history leading to the enactment ofWCA, explains the outline of WCA, discusses the potential impact to the existing co-operative lawsand concludes with some suggestions to make full use of WCA to operationalize workers co-operatives andenergize co-operative movement as a whole.